A sign of affection. 6 - Dashiell, Christine, 1984- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2023)
"Yuki...[has] always been deaf...But she's not used to English, so when a tourist from overseas asks for directions, she nearly panics...until a handsome stranger steps in to help. His name is Itsuomi, and it turns out he's a friend of a friend. A charismatic globetrotter, Itsuomi speaks three languages, but he's never had a deaf friend. The two feel drawn to each other and plan a date on a romantic winter's night, but Yuki's friend is afraid that she might be setting herself up to get hurt. Could this be something real? Or will these feelings melt away with the snow?"--